Coconut oil derived medium-chain triglycerides ameliorated memory deficits via promoting neurite outgrowth and maintaining gut homeostasis in 5×FAD mice - Chen, Ruiye; Li, Rui; Jiang, Jiahui; Zhou, Longjian; Zhao, Shuai; Zhang, Yi; Xia, Qiuyu; Yang, Zhiyou (Frontiers in Nutrition, 2025)
Alzheimer’s disease (AD) is a prevalent neurodegenerative disorder characterized by neurite atrophy, neuronal loss, and memory impairment. Medium-chain triglycerides (MCT), a type of fatty acid predominantly found in coconut oil, have been shown to improve metabolic syndrome as well as cognitive performance via ketone production in humans. Here, we investigated the protective effects of MCT on neurite atrophy and memory deficits in 5×FAD mice and elucidated the underlying mechanisms. First, virgin coconut oil (VCO), refined, bleached, and deodorized coconut oil (RBDCO), and MCT were orally administered to 6–8 months old 5×FAD mice for 9 consecutive weeks, the effects on cognition were then evaluated. MCT demonstrated superior effects compared to RBDCO and VCO in reducing Aβ levels, inhibiting hyperactivated microglia and astroglia, protecting neurons, and mitigating memory decline. Further, metagenomic analysis and RT-qPCR results revealed that MCT intervention increased the relative abundance of Akkermansia, reduced intestinal permeability, and elevated the concentration of short-chain fatty acids in the brain. Additionally, MCT treatment significantly protected primary cortical neurons against Aβ25-35-induced apoptosis and promoted neurite regeneration. Transcriptome and RT-qPCR data suggested that Ucp1 and Flor1 may be potential targets through which MCT exerts its neuroprotective effects. Our findings suggest that MCT may help prevent the progression of AD by promoting neurite outgrowth and maintaining gut homeostasis in 5×FAD mice, offering a theoretical foundation for the development of dietary therapies for AD.